Negotiations on Mashlahah and Customary Prohibitions on Praying for Dead Unpraying in Nagari Andaleh, Lima Puluh Kota Regency - Irianto, Marwit (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2026)
In the Nagari Andaleh community, Luak District, Lima Puluh Kota Regency, there is a rule that prohibits people from praying for the bodies of those who never prayed. This customary rule certainly raises widespread questions among the community about its applicability in general and specific contexts. Therefore, the purpose of this study is to describe the customary prohibition against praying for the bodies of people who did not pray, along with its limitations, and to examine the mashlahah (benefits) behind this customary rule. The research method used in this article is field research, in which primary research data was obtained directly from the local community through direct interviews. Secondary data was sourced from books, journals, and so on. The results of the study show that the customary rules that apply in Nagari Andaleh to people who do not pray when they die are that their bodies are not prayed over in congregation at the mosque and are not led by local scholars or authorities, but are still prayed over in a limited manner by their immediate family. From the perspective of mashlahah, this prohibition is in accordance with mashlahah mu'tabarah (mashlahah supported by nash) with the aim of protecting and preserving religion (hifzh al-din) at the dharuriyah (significant) level.